Sensing the framework state and guest molecules in MIL-53(Al) via the electron paramagnetic resonance spectrum of VIV dopant ions. Issue 36 (30th August 2017) - Nevjestić, Irena; Depauw, Hannes; Gast, Peter; Tack, Pieter; Deduytsche, Davy; Leus, Karen; Van Landeghem, Melissa; Goovaerts, Etienne; Vincze, Laszlo; Detavernier, Christophe; Van Der Voort, Pascal; Callens, Freddy; et al.
Abstract : The EPR spectrum of V IV dopant ions was used to discriminate different states of MIL-53(Al) and to detect oxygen gas. Abstract : X-ray diffraction (XRD) and electron paramagnetic resonance spectroscopy (EPR) were combined to study the structural transformations induced by temperature, pressure and air humidity of the "breathing" metal–organic framework (MOF) MIL-53(Al), doped with paramagnetic V IV ions, after activation. The correlation between in situ XRD and thermogravimetric analysis measurements showed that upon heating this MOF in air, starting from ambient temperature and pressure, the narrow pore framework first dehydrates and after that makes the transition to a large pore state (lp ). The EPR spectra of V IV O molecular ions, replacing Al–OH in the structure, also allow to distinguish the as synthesized, hydrated (np-h ) and dehydrated narrow pore (np-d ), andlp states of MIL-53(Al). A careful analysis of EPR spectra recorded at microwave frequencies between 9.5 and 275 GHz demonstrates that all V IV O in thenp-d andlp states are equivalent, whereas in thenp-h state (at least two) slightly different V IV O sites exist. Moreover, thelp MIL-53(Al) framework is accessible to oxygen, leading to a notable broadening of the V IV O EPR spectrum at pressures of a few mbar, while such effect is absent for thenp-h andnp-d states for pressures up to 1 bar.